Pedagogical problems of forming a sense of loyalty to the national army in students - Bobojonov N.N. (Zien Journals, 2021)
The article presents the results of research on the methods used to educate university students in the spirit of loyalty to the national army, to provide them with military knowledge, skills and abilities.
Keywords: National values; patriotism; sense of devotion; national dignity